Keabsahan Transaksi Spaylater pada Aplikasi Shopee dalam Jual-Beli Menurut Hukum Ekonomi Syariah - Bunga Pamela Anugraheni; Baidhowi Baidhowi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Technological advancements in the financial sector have led to various innovations, one of which is the SPayLater service, which allows consumers to make purchases using a deferred payment or installment system. In practice, this system raises various questions regarding the validity of transactions from the perspective of Islamic Economic Law, particularly in terms of compliance with the principles of sale and purchase contracts, as well as the potential presence of riba (usury) and gharar (uncertainty).This study aims to examine the validity of SPayLater transactions by analyzing the contracts used, potential violations of the principles of murabahah, ijarah, or qardh, and the extent to which this service complies with the conditions and pillars of sharia-compliant sale and purchase. The approach used is qualitative, analyzing Islamic legal literature, fatwas issued by Indonesia’s National Sharia Council (DSN-MUI), as well as case studies of SPayLater services in Indonesia. The findings indicate that SPayLater transactions have the potential to involve riba if there are non-transparent additional charges. Furthermore, late payment penalties and unclear contracts may give rise to gharar, which could render the transaction invalid under Islamic law. Therefore, it is necessary to modify the contracts to better align with sharia principles and to enhance transparency in the payment mechanisms in order to avoid elements of riba and gharar.